Hydro-morphological and hydrochemical conditions of the Parsęta River - Szpikowski, Józef; Szpikowska, Grażyna (Bulletin of Geography. Physical Geography Series, 2018)
Rivers are hydro-morphologically assessed in line with the Water Framework Directive. In order to assess the quality of the Parsęta River environment, the River Habitat Survey method was applied. The research studies conducted in June 2016, apart from hydro-morphological issues, also covered measurements and laboratory analyses on the quality of its waters. There were 24 measuring sections selected along the whole river. The selection of these sections took into account the representativeness of genetically various types of river valley, its size and discharge as well as the variability of anthropogenic pressure. The conducted assessment showed that the Parsęta River is characterised by a varying degree of its natural quality (its HQA index ranged 17-61) and a variable but generally low modification of its valley (its HMS index ranged 0-33). 79% of the analysed sections was classified to the second (II) and third (III) hydro-morphological class while 8% - to the first (I) one and 13% - to the fourth (IV) one. The central section of the Parsęta River is characterised by the highest degree of naturalness and the smallest degree of its transformation. The river valley sections of kettle-hole origin are more transformed than the ones of fluvial origin. The quality of the Parsęta River waters assessed on the grounds of the their physico-chemical parameters indicates that the river is in good condition. The individual river water parameters are most often within the first (I) and second (II) classes. The lowered quality of waters below the 'good' level is related to the concentration of phosphates beyond the second (II) class and includes a 15 km stretch of the river below Białogard. The river section with a high degree of hydro-morphological naturalness is characterised by the worst quality of waters.